What Is the Benefit of Community Benefits? Exploring Local Perceptions of the Provision of Community Benefits from a Commercial Wind Energy Project. (2nd October 2017) - Macdonald, Catriona; Glass, Jayne; Creamer, Emily
ABSTRACT: Where community ownership of renewable energy projects is not feasible, there remains potential for residents to profit from locally sited projects through a 'community benefits' package from a commercial developer, usually as an annual cash payment to a community organisation. Despite support from policy-makers and developers for community benefit packages, the relationship between the benefit package and acceptance of renewable energy projects is not straightforward. Drawing on semi-structured interviews with local residents and other community actors near a wind development in central Scotland, this paper examines the 'process' and 'outcome' dimensions of the design and provision of community benefits, and considers how the relationship between these two dimensions affects local perceptions of the benefit of community benefits. Analysis of interviewees' perceptions of the community engagement 'process' at the planning stage and the community benefit package 'outcome' reveals how a poorly defined engagement process, combined with a benefits package that is not deemed suitable for the needs of the community, can lead to negative perceptions of the project, even when these were initially positive. These findings have implications for renewable energy policy in Scotland, particularly as there is currently no legal obligation for developers to consult communities on community benefit arrangements.